P–546 Exome sequencing and preimplantation genetic testing for unexplained recurrent fetal malformations. (6th August 2021) - Ev. M, G; Morales, R; Lledo, B; Ortiz, J A; Lozano, F M; Fuentes, A; Llacer, J; Bernabeu, A; Bernabeu, R
Abstract: Study question: Could patient suffering unexplained recurrent fetal malformations be benefit of PGT-M by exome sequencing mutations identification? Summary answer: Patients suffering unexplained recurrent fetal malformations could be benefit of the use of exome sequencing in combination to PGT-M to have a healthy live birth. What is known already: Fetal malformations account for approximately 3% of live births and causes include: chromosomal abnormalities, exposure to toxic substances or teratogens and infections. Recently, studies have shown that several monogenic diseases are linked to fetal abnormalities. However, because of the large number of potential genes, genetic testing is challenging. Exome sequencing is widely used to detect genetic mutations and has emerged as a useful tool for finding the genetic cause of fetal abnormalities. The aim of this study was to show how exome sequencing in patients suffering unexplained recurrent fetal malformations in combination to PGT-M could lead to successful healthy newborn. Study design, size, duration: Case report of a non-consanguineous couple with unexplained, recurrent fetal malformations. Couple were recruited during clinical consultation for unexplained recurrent fetal malformations at a private reproductive medicine clinic. The couple had two malformed fetus with the same congenital abnormalities: hydrocephalus, cerebellar vermis agenesis, cerebellar hypoplasia and enlarged cisterna magna. Patients signed written informed consent regarding to exome testing. For fetal sample, informed consent was obtained from parents. Participants/materials, setting, methods: Sample of the affected fetus were provided. Parental genomic DNA was extracted from peripheral blood. Exome sequencing was performed using TrusightOne (Illumina®). FASTAQ data were processed through BWA and GATK algorithm. VCF files were analysed using Variant Interpreter software. After genetic counselling, PGT-M was performed using linkage polymorphic markers analysis and mutation sequencing. Embryo biopsy was carried at blastocyst stage. Embryos were vitrified and one healthy embryo was thaw and transfer in a subsequent cycle. Main results and the role of chance: An homozygous novel pathogenic mutation c.641 C>T (p.Ala214Val) in FVLCR2 gene was found. The parents were heterozygous carriers revealing that the detected variant follow an autosomal recessive pattern. The FLVCR2 (14q24.3) gene encodes a transmembrane protein that belongs to the major facilitator superfamily of secondary carriers that transport small solutes in response to chemiosmosis ion gradients, such as calcium. Mutations in this gene are related to fetal central nervous system defects. This disorder is diagnosed prenatally and is lethal. PGT-M was recommended during genetic counselling. After control ovarian stimulation 14 oocytes were retrieved and finally 4 embryos were suitable for embryo biopsy at blastocyst stage. One embryo was diagnosed as healthy, two affected and one heterozygous carrier. The healthy embryo was thaw and transferred and a healthy male baby was born. Limitations, reasons for caution: Exome sequencing has technical limitations: only covers mutations in coding regions and does not cover noncoding regions of the genome. It also cannot reliably detect copy-number variants at single gene level. Wider implications of the findings: This study offers strong evidence of exome-sequencing as a new diagnostic strategy and powerful tool discovering the underlying etiology of recurrent fetal malformations and identifying new genes important for human development. Using this strategy in combination with PGT-M, clinicians can help couples with recurrent fetal malformations to have healthy newborns. Trial registration number: Not applicable